Precise Layer Control of MoTe2 by Ozone Treatment - Qiyuan Wang; Jing Chen; Youwei Zhang; Laigui Hu; Ran Liu; Chunxiao Cong; Zhi-Jun Qiu (Nanomaterials, 2019)
Transition metal dichalcogenides (TMDCs) demonstrate great potential in numerous applications. However, these applications require a precise control of layer thickness at the atomic scale. In this work, we present an in-situ study of the self-limiting oxidation process in MoTe2 by ozone (O3) treatment. A precise layer-by-layer control of MoTe2 flakes can be achieved via multiple cycles of oxidation and wet etching. The thinned MoTe2 flakes exhibit comparable optical properties and film quality to the pristine exfoliated ones. Besides, an additional p-type doping is observed after O3 oxidation. Such a p-doping effect converts the device properties of MoTe2 from electron-dominated to hole-dominated ambipolar characteristics.